Rf circuit implementation of a real-time frequency spread emulator - Karabacak, Murat; Mohammed, Ahmed Hossam; Özdemir, Mehmet Kemal; Arslan, Hüseyin (IEEE-Institute of Electrical and Electronics Engineers Inc, 2018)
Despite their reliability, on-site measurements are time-consuming and costly actions for the evaluation of new devices. Channel emulators are widely utilized measurement instruments to generate desired environmental channel effects in laboratory environments. Within these instruments, baseband emulators are expensive, and reverberation chambers provide limited control of the channel. However, radio-frequency (RF) circuit implementation of channel emulators provides an affordable and easy tool to test performances of new systems and methods under different channel effects. In this paper, a new RF domain Doppler emulator, which is compact and easy to control, is presented for measuring signal characteristics under frequency dispersive channel conditions. The circuit has been implemented using variable attenuators, switches, and power splitters to emulate the Doppler spread of air-ground channels, and the performance is evaluated through measurements. It is observed that the emulator indeed generates the desired Doppler model close enough to replicate environmental channels for mobile applications in laboratory environments.
WOS: 000417961300025
Keywords: Channel Emulator; Doppler Spread; Fast Fading Emulator; High-Speed Communication; Radio-Frequency (RF) Circuit